The XBB.1.5 slightly increase the binding affinity for host receptor ACE2 and exhibit strongest immune escaping features: molecular modeling and free energy calculation - Suleman, Muhammad; Murtaza, Aneela; , Maria; Khan, Haji; Rashid, Farooq; Alshammari, Abdulrahman; Ali, Liaqat; Khan, Abbas; Wei, Dong-Qing (Frontiers in Molecular Biosciences, 2023)
The current XBB variant of SARS-CoV-2 with the strongest immune escaping properties is currently the most dominant variant circulating around the world. With the emergence of XBB global morbidities and mortalities have raised again. In the current scenario, it was highly required to delineate the binding capabilities of NTD of XBB subvariant towards human neutralizing antibodies and to dig out the binding affinity of RBD of XBB subvariant with ACE2 receptor. The current study uses molecular interaction and simulation-based approaches to decipher the binding mechanism of RBD with ACE2 and mAb interaction with NTD of the spike protein. Molecular docking of the Wild type NTD with mAb revealed a docking score of -113.2 +/- 0.7 kcal/mol while XBB NTD docking with mAb reported -76.2 +/- 2.3 kcal/mol. On the other hand, wild-type RBD and XBB RBD with ACE2 receptor demonstrated docking scores of -115.0 +/- 1.5 kcal/mol and -120.8+/-3.4 kcal/mol respectively. Moreover, the interaction network analysis also revealed significant variations in the number of hydrogen bonds, salt-bridges, and non-bonded contacts. These findings were further validated by computing the dissociation constant (KD). Molecular simulation analysis such as RMSD, RMSF, Rg and hydrogen bonding analysis revealed variation in the dynamics features of the RBD and NTD complexes due to the acquired mutations. Furthermore, the total binding energy for the wild-type RBD in complex with ACE2 reported -50.10 kcal/mol while XBB-RBD coupled with ACE2 reported -52.66 kcal/mol respectively. This shows though the binding of XBB is slightly increased but due to the variation in the bonding network and other factors makes the XBB variant to enter into the host cell efficiently than the wild type. On the other hand, the total binding free energy for the wildtype NTD-mAb was calculated to be -65.94 kcal/mol while for XBB NTD-mAb was reported to be -35.06 kcal/mol respectively. The significant difference in the total binding energy factors explains that the XBB variant possess stronger immune evasion properties than the others variants and wild type. The current study provides structural features for the XBB variant binding and immune evasion which can be used to design novel therapeutics.